Current trends and future prospects of lipstatin: a lipase inhibitor and pro-drug for obesity. Issue 106 (14th October 2015) - Kumar, Punit; Dubey, Kashyap Kumar
Abstract : A review of the implications and causes of obesity, the status of antiobesity drugs, the mechanism of inhibition of pancreatic lipases, the biosynthesis of lipstatin and the present status of lipstatin production. Abstract : Obesity is an alarming state caused by an energy imbalance. It is associated with cardiovascular diseases, type-II diabetes, and cancer. Physical inactivity and overeating are the main causes of obesity but scientific reports also support the involvement of Single Nucleotide Polymorphisms (SNPs) in adiposity. Lipids are known to produce more energy than sugars and proteins, hence controlling the digestion of dietary lipids is a promising approach to treat obesity. Lipstatin is a β-lactone molecule which controls the digestive activity of pancreatic lipases and thus controls the absorption of fat in the small intestine. The three dimensional structure of pancreatic lipase revealed that its active site is masked by a lid domain which is opened by the action of bile salt micelles and colipase. Lipstatin is supposed to inhibit the catalytic activity of pancreatic lipase by acylation of the serine residue present in the active site. A binding study suggests that one molecule of lipstatin binds with one molecule of lipase. Tetra-hydro-lipstatin is an Active Pharmaceutical Ingredient (API) of lipstatin which is utilized in antiobesity medicines. Lipstatin is a natural product produced from Streptomyces toxytricini but poor productivity heightens the cost. The mechanism of lipstatin biosynthesis in bacteria is still unexplored. However, the acyl-coenzyme A carboxylase (ACCase) complex plays a key role in lipstatin biosynthesis. The present review focuses on the implications and causes of obesity, the status of antiobesity drugs, the mechanism of inhibition of pancreatic lipases, the biosynthesis of lipstatin and the present status of lipstatin production.